CALM & CARE: A CHILD-CENTRED DIGITAL THERAPY PLATFORM FOR MENTAL HEALTH (Journal of Digital System Development, 2024)
Mental health, as critical as physical well-being, has gained significant importance during the COVID19 pandemic. Moreover, pandemic-induced lockdowns have exacerbated mental health issues, including suicides, spousal violence, and domestic bullying. Consequently, the demand for digital therapeutics has surged, manifesting as mobile and web applications and facilitating remote access to support. However, children have been underserved in this category despite their vulnerability to the emotional consequences of school closures and caregiver distress. This study's objectives and methodology encompassed developing a child centric digital therapy mobile application, conducting usability testing for optimal user-friendliness, creating content compliant with industry standards, gathering user feedback for improvements and providing ongoing maintenance for the application's effectiveness. The resulting 'Calm & Care' prototype empowers parents to authorise counselling sessions and motivational content for their children at home. Ten families participated in user testing, yielding positive feedback praising the vibrant interface, child-friendly visuals, and simplified language for an enhanced user experience. 'Calm & Care' can enable local clinics to accept mental health patients with lower infection risks and increase treatment success. This research underscores the pivotal role of digital solutions in addressing children's mental well-being during the pandemic.